Therapeutic effects of mesenchymal stem cell-derived extracellular vesicles in osteoporosis models: a systematic review and meta-analysis of preclinical studies - Zhang, Ying; Liu, Yi; Wang, Shaoyun; Wang, Chao (Frontiers in Endocrinology, 2025)
ObjectiveTraditional pharmacological treatments for osteoporosis face challenges due to various limitations, including long-term safety concerns and limited bone anabolic effects. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have emerged as a promising cell-free alternative therapy. However, their preclinical efficacy and the factors driving heterogeneity still require systematic evaluation.MethodsA systematic search was conducted in PubMed, EMBASE, Cochrane Library, and Web of Science (from inception to February 2025). Two independent authors performed literature screening, data extraction, and risk of bias assessment. A random-effects model was used to pool and analyze bone mineral density (BMD), bone volume fraction (BV/TV), trabecular/cortical structural parameters, and biomechanical test results. Publication bias was assessed using funnel plots and Egger’s test, while leave-one-out sensitivity analysis was performed to evaluate the stability of the results. Subgroup analyses were conducted based on animal type, EVs source, synthesis method, engineering approach, intervention route, frequency, and treatment duration.ResultsA total of 17 studies were included. The results demonstrated that, compared to the control group, MSC-EVs significantly increased BMD, BV/TV, trabecular number (Tb.N), trabecular thickness (Tb.Th), cortical thickness (Ct.Th), mineral apposition rate (MAR), and the ultimate load-bearing capacity of the femur, while reducing trabecular separation (Tb.Sp). Significant heterogeneity and publication bias were observed in all analyses. Sensitivity analysis confirmed the robustness of all results.ConclusionsMSC-EVs demonstrate significant improvements in preclinical osteoporosis models, highlighting its potential for clinical translation. However, further standardized studies are needed to evaluate the long-term efficacy and safety of MSC-EVs.